2013
DOI: 10.5430/afr.v2n3p1
|View full text |Cite
|
Sign up to set email alerts
|

Web-based Disclosures and Their Determinants: Evidence from Listed Commercial Banks in Nepal

Abstract: What is the extent of disclosure, using the Internet, by commercial banks listed on Nepal Stock Exchange? What are the determinants of varying levels of web-based disclosure by those companies? These were the research questions addressed in this paper. All 23 commercial banking companies were found to have maintained their own websites and annual reports were made available in compliance with directive number 4 of Nepal Rastra Bank. A 50 items disclosure index, based on existing literature modified for Nepal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 35 publications
3
17
0
3
Order By: Relevance
“…the greater the size of the company, the more extensive the IFR disclosure is. This results provide empirical support to the results of previous studies (Lestari & Chariri 2007;Prasetya and the governor 2012;Pubandani & Restuti 2013;Umoren & Asogwa 2013;Sharma 2013;Aziz, Ariffin & Mohamed 2009;Türel 2010;Almilia 2008;Chatterjee & Hawkes 2008;Pervan 2006;Ponte & Rodríguez 2002;Hanifa and Rashid 2005). It can be concluded that the greater the company size, the more extensive and comprehensive the duty to report to their stakeholders.…”
Section: Company Size and Internet-financial Reporting Disclosure Sizesupporting
confidence: 88%
“…the greater the size of the company, the more extensive the IFR disclosure is. This results provide empirical support to the results of previous studies (Lestari & Chariri 2007;Prasetya and the governor 2012;Pubandani & Restuti 2013;Umoren & Asogwa 2013;Sharma 2013;Aziz, Ariffin & Mohamed 2009;Türel 2010;Almilia 2008;Chatterjee & Hawkes 2008;Pervan 2006;Ponte & Rodríguez 2002;Hanifa and Rashid 2005). It can be concluded that the greater the company size, the more extensive and comprehensive the duty to report to their stakeholders.…”
Section: Company Size and Internet-financial Reporting Disclosure Sizesupporting
confidence: 88%
“…Also, results indicate that larger banks are more transparent since positive relationship was confirmed for the size variable. Similar research was conducted on a sample of commercial banks from Nepal [20]. With regard to selected determinants of bank Internet reporting variables foreign ownership, board independence and bank size were found to be significantly associated with web-based disclosure.…”
Section: Previous Research On Internet Financial Reporting Of Banksmentioning
confidence: 64%
“…The universe of banks involved in the study is listed in The IC disclosures of the Nigerian banks increased moderately over the four years. Human and structural capital are the most disclosed items Sharma (2013) Analyze the extent of disclosure, using the internet, by commercial banks in Nepal…”
Section: Methodological Approachmentioning
confidence: 99%